Social Consciousness in the Plays of Dr. Nawaz Kavesh - Naseem, Ejaz; Hussain, Ahmad (sourcecoder, 2022)
Dr. Nawaz Kavesh is a multidimentional personality. The atmost prominent aspect of his personality is sincerity. This sincerity seems throughout in his teaching, research, criticism and creativity. It included the inauguration of radio Pakistan in Bahawalpur and its stability. He has a particular position in poetry. In the fiction writing, he chose the genre of drama. His dramas harbours the intense feeling of high human values. He univerled and exposed the hunger, imprisonment, economics exploitation, instability of relations poverty and moral bankruptey. In his dramas social and economic consciousness exploded its rays everywhere found in them. In this research article in the dramas of Dr. Nawaz Kavesh Social consciousness will be analyzed.